Fostering Employee Well-Being in High-Pressure Work Environments: Lessons from Tax Service Offices - Lestari, Hera Kurnia; Putranta, Martinus Parnawa (Soegijapranata Catholic University, 2025)
This study investigates the effects of job stress and workplace loneliness on job satisfaction and psychological well-being among Account Representatives in Indonesian Tax Service Offices. A quantitative cross-sectional approach was employed, collecting data from 125 respondents using a Likert-scale-based questionnaire. The analysis utilized Partial Least Squares Structural Equation Modeling (PLS-SEM) to examine the relationships between variables. The findings indicate that job stress does not significantly influence job satisfaction or psychological well-being, suggesting that contextual factors, such as organizational support or employee adaptability, may mitigate its effects. Conversely, workplace loneliness has a significant negative impact on both job satisfaction and psychological well-being, highlighting the importance of fostering social connections in the workplace. Moreover, job satisfaction is found to positively and significantly influence psychological well-being.These results underscore the need for organizations to create inclusive and supportive environments that reduce workplace loneliness, enhance job satisfaction, and promote psychological well-being. This study contributes to the literature by offering insights into these dynamics within the unique context of Indonesian government organizations. Limitations include the cross-sectional design and the focus on a specific population, suggesting future research explore mediating and moderating factors or adopt longitudinal approaches.